Exploring the Components of Individual Virtual Competence in Virtual Team Members by Generation - Paul, Ravi; Tuttle, Claire (American Journal of Management, 2020)
This research seeks to determine the influence of aspects of Individual Virtual Competence based on the generation of a virtual team member. We empirically tested several hypotheses with data collected from 262 professionals with virtual teams experience across three generations. The results indicate that remote work self-efficacy (RWSE) impacts IVC more significantly for Generation X than for Baby Boomers and Millennials. By contrast, virtual social skill (VSS) impacts the IVC of Baby Boomers more than it does for Generation X or millennials. The findings are important for any individuals engaged in virtual teamwork, both as team members and team managers.